The Use of Think Pair Share Combined with Video to Improve Speaking Skill in SMA (SLUA) Saraswati 1 Denpasar - Yudiartawan, I Nyoman; Putu Arsana, Anak Agung; Krismayani, Ni Wayan (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2024)
This research was conducted to figure out whether the subjects’ speaking skill can be improved use the Think Pair Share Combined with Video. The subjects were the eighth-grade students of SMA (SLUA) Saraswati 1 Denpasar. There were 22 subjects which consist of 16 females and 6 males. The design was classroom action research design. The data which were needed for the present study were collected through Think Pair Share Combined with Video technique in two cycles and the obtained data was analyzed quantitively from the pre-test, post-test 1 and post-test 2; then qualitatively from the questionnaire. The result showed that the students’ mean score had significant improvement from the pre-test was 63.71 to 71.5 in post-test 1, and 80.13 in post-test 2. Furthermore, to collect the additional supporting data; the researcher administered the questionnaire at the end of cycle II. It showed positive responses toward the implementation of Think Pair Share Combined with Video. In conclusion, it could be concluded that speaking skills of the tenth-grade students of SMA (SLUA) Saraswati 1 Denpasar in academic year 2022/2023 could be improved use Think Pair Share Combined with Video.